Cloud Base Height at the Thule High Arctic Atmospheric Observatory (THAAO_CBH) - Di Iorio, Tatiana; di Sarra, Alcide; Pace, Giandomenico; Meloni, Daniela; Muscari, Giovanni; Di Liberto, Luca; Calì Quaglia, Filippo; Iaccarino, Antonio (2022)
Cloud Base Height at the Thule High Arctic Atmospheric Observatory (THAAO_CBH)